Effects of Hematocrit on Blood Flow Through A Stenosed Human Carotid Artery - Onitilo, Sefiu; Usman, Mustapha; Daniel, Deborah (Iraqi Journal of Science, 2020)
In this paper, the effects of hematocrit of red blood cells on blood flow through a stenosed human carotid artery was considered by taking blood as a Newtonian fluid. The governing equations on blood flow were derived. The mathematical content involved in the equations are the variables of interest such as number of stenosis , percentage of hematocrit of red blood cells in the blood, flow rate, wall shear stress, and viscosity of the blood. Guided by medical data collected on the constraint of blood flow in stenosed human carotid arteries, the governing equations were used to check the effects of pressure gradient, wall shear stress, velocity, and volumetric flow rate of blood in the human carotid arteries. Also, the one-dimensional equation for the steady and axially symmetric flow of blood through an artery was transformed using Einstein’s coefficient of viscosity and hematocrit of red blood cells with the help of the boundary conditions. The effects of hematocrit on the blood flow characteristics are shown graphically and discussed briefly. It was discovered that the resistance increases as the level of hematocrit increases. Also, the wall shear stress decreases with the increase in the hematocrit level of the red blood cells.